A biopsychosocial analysis of sexuality in adult males and their partners after severe traumatic brain injury. (28th July 2016) - Bivona, Umberto; Antonucci, Gabriella; Contrada, Marianna; Rizza, Federica; Leoni, Federica; Zasler, Nathan D.; Formisano, Rita
Abstract: Purpose : The primary aim of this study was to investigate changes in sexual function in males and their partners following severe TBI. Secondary aims of the study were to explore the relationship between selected sociodemographic, emotional/behavioural and sexual function variables. Methods : Twenty males with a history of severe TBI and 20 healthy controls (HC) and their respective partners were recruited. Sexual life was assessed with the Sexuality Evaluation Schedule Assessment Monitoring (SESAMO). Study participant level of self-awareness was evaluated by the Awareness Questionnaire, whereas their neuropsychiatric and psychopathological statuses were assessed by the NPI, the HAM-D and STAI. Results : A reduction in desire and frequency of sexual intercourse was found in all survivors and their partners. Moreover, higher levels of survivor depression correlated with lower partner harmony. Survivor feelings toward their partners gradually decreased over time, as did the ability to make decisions as a couple. The comparison with HC couples revealed that both survivors' and their partners' exaggerated the extent of disease. Conclusions : After male severe TBI, men appear to have a reduced quality of their sexual life, which may be more a result of relationship dysfunction than a sexual performance deficit related to their brain injury history.